Nanotechnology-based herbal medicine: Preparation, synthesis, and applications in food and medicine - Farhang H. Awlqadr; Kithar Rasheed Majeed; Ammar B. Altemimi; Arkan Mohammed Hassan; Syamand Ahmed Qadir; Mohammed N. Saeed; Aryan Mahmood Faraj; Tablo H. Salih; Alaa Jabbar Abd Al‐Manhel; Mazin A.A. Najm; Efstathia Tsakali; Jan F.M. Van Impe; et al. (Journal of Agriculture and Food Research)
Nanotechnology has instigated profound developments among herbal medicineregarding bioavailability, stability, and therapeutic efficacy. This review deals with nano-herbal formulations' preparation, applications, and therapeutic capabilities for medical problems and foods like food packaging and preservation. The formulations are developed using advanced nanotechnology techniques, such as solvent evaporation, nanoemulsion formation, and encapsulation. Phytosomes, liposomes, nanocapsules, and nanoemulsions have ensured that bioactive ingredients' stability has been secured, bioavailability and targeted administration have been improved, and negative side effects have been cut considerably. The ability of nanoherbal formulations to deliver drugs to tumor cells in an improved permeability and retention manner, such as, cancer therapy while minimizing tissue damage, has been largely practiced in many laboratories. Enhanced drug solubility, distribution to the site of interest, and successful therapeutic outcomes have had a major impact on inflammatory disorders, cardiovascular diseases, diabetes, skin problems, and neurodegenerative diseases. Dendrimers and solid lipid nanoparticles transport anti-inflammatory and antioxidant substances, whereas polymeric nanoparticles protect against Alzheimer's and Parkinson's diseases. Nanocarriers increase the absorption of curcumin and resveratrol, decreasing oxidative stress and improving cardiac function. Nanotechnology has used such reinforcing materials to improve the performance of protective food packages and, consequently, ensure their longer service time. On the one hand, antimicrobial and antioxidant herbal nanoparticles will prevent spoilage and degradation during storage.On the other hand, nanoemulsions form a medium for vitamins, minerals, and antioxidants to be bioavailable in fortified meals. The following practices have contributed to preserving food products' nutritional and functional attributes. Nonetheless, nanotechnology has found its way into these chemical compositions, bringing about the issues of scaling up, cost-efficiency, regulatory compliance, and safety concerns. Biodistribution, metabolism and the coccion of long-term effects studies must confirm safe and sustainable usage. To stimulate full utilization of nanotechnology in medicine and food science, further study must be undertaken to clear the existing drawbacks and discover other fields of the most appropriate applications of nanotechnology. Nanotechnology and herbal medicine join forces and form a potent medical and nutritional solution to various diseases, food production, and conservation. Such advancements would modify treatment and nutritional strategies, allowing a more secure, effective, and long life.